2020
DOI: 10.1038/s41598-019-56970-2
|View full text |Cite
|
Sign up to set email alerts
|

Mangosteen pericarp components alleviate progression of prostatic hyperplasia and mitochondrial dysfunction in rats

Abstract: prostatic hyperplasia, characterized by progressive hyperplasia of glandular and stromal tissues, is the most common proliferative abnormality of the prostate in aging men. A high-fat diet (HfD) usually is a major factor inducing oxidative stress, inflammation, and an abnormal state of the prostate. Mangosteen pericarp powder (Mpp) has abundant xanthones which can be antioxidant, anti-inflammatory, and antiproliferative agents. Therefore, the purpose of this study was to research whether MPP supplementation ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…It is also known as a hallmark for non-alcohol fatty liver disease. The administration of mangosteen pericarp showed that it was able to reverse hepatic steatosis by increasing the level of antioxidants (GSH, GPx, SOD, and CAT) and decreasing lipid peroxidation levels, plasma-free fatty acids, and hepatic triglyceride levels (Tsai et al, 2016).…”
Section: Mangosteen Antioxidant Activity Toward Liver and Kidneymentioning
confidence: 99%
See 3 more Smart Citations
“…It is also known as a hallmark for non-alcohol fatty liver disease. The administration of mangosteen pericarp showed that it was able to reverse hepatic steatosis by increasing the level of antioxidants (GSH, GPx, SOD, and CAT) and decreasing lipid peroxidation levels, plasma-free fatty acids, and hepatic triglyceride levels (Tsai et al, 2016).…”
Section: Mangosteen Antioxidant Activity Toward Liver and Kidneymentioning
confidence: 99%
“…A total of four studies tested the mangosteen antioxidant activity toward liver in the acute liver injury model (Wang et al, 2018;Yan et al, 2018), chronic liver injury model (Wang et al, 2019), and hepatic steatosis model (Tsai et al, 2016). The acute and chronic liver injury could occur when the liver is exposed to chemical stresses, such as alcohol and drug consumption, and the difference between the two is the duration of stress exposure (Wang et al, 2018).…”
Section: Mangosteen Antioxidant Activity Toward Liver and Kidneymentioning
confidence: 99%
See 2 more Smart Citations
“…4 Pathologically, it is associated with an increase in proliferating cells and the establishment of inflammation in the prostate tissue. 5,6 The inflammatory environment and uncontrolled cell proliferation leads to tumorigenesis. 5 The experimental models are important in the study of this disorder that can be induced by androgen analogs.…”
Section: Introductionmentioning
confidence: 99%